Trafficking for sexual exploitation: Approach to its relationship with prostitution and consumer behavior - Rodríguez Vásquez, Julio (2016)
This article studies the relationship between trafficking for sexual exploitation and prostitution. The study of this relationship will focus on the positions advocating the criminalization of prostitution and/or conduct consumer / customer. This analysis leads us to analyze, first, the crime of trafficking in persons. In this line, we will discuss the issue on the legal right; and its characteristic as complex crime comprising various means, behaviors and purposes. Second, we will approach the four kinds of legislative policies prostitution: reglamentarism, prohibitionist, abolitionist and regulationism. The critical study of these models will allow us to outline a tentative conclusion on the criminalization of prostitution and consumer behavior / customer.